Proceedings of the Fourteenth ACM Conference on Hypertext and Hypermedia 2003
DOI: 10.1145/900051.900098
|View full text |Cite
|
Sign up to set email alerts
|

Link analysis for collaborative knowledge building

Abstract: We present an ongoing research project utilizing navigation and hyperlink data to aid collaborative knowledge building. We allow collaborators to personally organize documents and other research resources and make references to them. We combine their personal organizations and references to develop a unified, hierarchical categorization of these resources. We analyze collaborators' navigations to identify prominent research activities as well as the key documents related to these activities. We examine promine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Different clustering techniques use different pair-wise similarity measures such as cosine and Euclidean similarities, and different group-wise similarity methods such as average linkage and centroid. Wu et al (2003Wu et al ( , 2004 have shown that Jaccard similarity measure and the average linkage method perform better than other alternatives in producing hierarchies from categorical data. Through evaluation we have confirmed that the combination of Jaccard similarity measure and average linkage method performs better, i.e.…”
Section: Ontology Generationmentioning
confidence: 99%
“…Different clustering techniques use different pair-wise similarity measures such as cosine and Euclidean similarities, and different group-wise similarity methods such as average linkage and centroid. Wu et al (2003Wu et al ( , 2004 have shown that Jaccard similarity measure and the average linkage method perform better than other alternatives in producing hierarchies from categorical data. Through evaluation we have confirmed that the combination of Jaccard similarity measure and average linkage method performs better, i.e.…”
Section: Ontology Generationmentioning
confidence: 99%
“…In Wu et al [9] defined personalization as a system development approach for designing information systems that change configurations based on each user's needs and preferences. Kramer et al [10] described web personalization as a toolbox of technologies and application features used in the design of an end-user experience.…”
Section: Web Personalizationmentioning
confidence: 99%
“…User directed linking behavior has also been widely studied in a variety of contexts, such as [30][24] [31]. However, none of these systems have been implemented with smart-objects similar to buckets.…”
Section: Related Workmentioning
confidence: 99%